2022
DOI: 10.1186/s12876-022-02622-1
|View full text |Cite
|
Sign up to set email alerts
|

The hsa_circ_0039857/miR-338-3p/RAB32 axis promotes the malignant progression of colorectal cancer

Abstract: Background Colorectal cancer (CRC) is a prevalent malignancy of the gastrointestinal. Circular RNAs (circRNAs) act as important roles in CRC malignant progression. However, the role of circ_0039857 in CRC is still unclear. Therefore, this study aimed to explore the function and mechanism of hsa_circ_0039857 in the CRC. Methods The mRNA and protein expression were measured via RT-qPCR. RNase R assay and Actinomycin D were employed to evaluate the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another study performed by Tang et al has shown that miR-370 downregulation in lung cancer tissues elicits antitumor activity. Transfection with miR-370 cells inhibits cell proliferation, invasion, and migration of A549 lung cancer cells (Tang et al, 2022). In gastric cancer tissues, miR-378a-3p is significantly downregulated.…”
Section: Downloaded Frommentioning
confidence: 96%
“…Another study performed by Tang et al has shown that miR-370 downregulation in lung cancer tissues elicits antitumor activity. Transfection with miR-370 cells inhibits cell proliferation, invasion, and migration of A549 lung cancer cells (Tang et al, 2022). In gastric cancer tissues, miR-378a-3p is significantly downregulated.…”
Section: Downloaded Frommentioning
confidence: 96%